Establishing The Degree of Relationship in Cryptolepis sanguinolenta (Lindl.) Schter.: An Antimalaria Plant Using Cluster Analysis - AMEYAW, Y.; AKOTOYE, H.K.; PAPPOE, A.N.M.; OPOKU BOACHEN, Y.; EYIAH-BEDIAKO, F. (Asian Journal of Chemistry, 2010)
Cluster Analysis was used to determine the levels of similarities or the degree of resemblance in Cryptolepis sanguinolenta (Lindl.) Schter., an antimalarial plant. The results showed that within the populations, Pepease and Mamfe showed a closer association or resemblance than of Abonse in all the morphological characters. The degree of relationship or resemblance of the populations in terms of anatomical characters was much varied. With Pepease and Abonse populations closely related than Mamfe in terms of the root fibre length with reference to the root vessel element, Mamfe and Abonse populations were much related whiles Pepease was loosely related and finally, Mamfe and Pepease populations also closely related than Abonse in terms of the root prismatic crystal length.